2007
DOI: 10.1071/sr07024
|View full text |Cite
|
Sign up to set email alerts
|

Categorisation of soils based on potassium reserves and production systems: implications in K management

Abstract: Crop fertilisation with potassium in rainfed agriculture in India is not practised, merely on the assumption that Indian soils are rich in potassium and crops do not need external K supply. However, under continuous cropping in rainfed regions, huge crop K removals are reported, up to 150–200 kg/ha annually, depending upon amount and distribution of rainfall and biomass production. Thus, most of the crops essentially deplete soil K reserves. The present study evaluates the soil K reserves under diverse rainfed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…). Other studies (Rezapour et al, 2010;Srinivasarao et al, 2007;Zhang et al, 2009) have also reported significant differences of total K content among different soil types, mainly due to soil texture and soil mineralogy.…”
Section: Soil Properties and Potassium Statusmentioning
confidence: 96%
“…). Other studies (Rezapour et al, 2010;Srinivasarao et al, 2007;Zhang et al, 2009) have also reported significant differences of total K content among different soil types, mainly due to soil texture and soil mineralogy.…”
Section: Soil Properties and Potassium Statusmentioning
confidence: 96%
“…The available K in the watershed varied between 84 and 611 kg ha" . The general mind set of the region's farmers is that these soils are rich in available K; consequently, they do not apply K fertilizer (Srinivasarao et al, 2007). Long-term cultivation without any K fertilizer as well as the strong leaching process (Sun et al, 2000) might have caused deficiencies in available K (52% of samples were <280kgha"), causing a strong spatial variation within the watershed.…”
Section: Spatial Variability Of Soil Propertiesmentioning
confidence: 99%
“…The NH 4 OAc-K content varied widely and ranged from 2.3 mg kg −1 to as high as 369 mg kg −1 . Non-exchangeable K in most of the samples ranged from low to medium (Srinivasarao et al, 2007;Walter et al, 2011). About 76 % of the samples were "low" (non-exchangeable K contents <300 mg kg −1 ) in the non-exchangeable K supply, while 20 % of samples were "medium" (300-600 mg kg −1 ) and only 4 % of samples were in the "high" (> 600 mg kg −1 ) category.…”
Section: Potassium Status Of Soilsmentioning
confidence: 99%
“…About 76 % of the samples were "low" (non-exchangeable K contents <300 mg kg −1 ) in the non-exchangeable K supply, while 20 % of samples were "medium" (300-600 mg kg −1 ) and only 4 % of samples were in the "high" (> 600 mg kg −1 ) category. About 40 % of samples were "low" in plant-available K (exchangeable K content below 50 mg kg −1 ), 40 % of samples were "medium" (K content of 50-125 mg kg −1 ) and only 20 % of samples were "high" (K content > 125 mg kg −1 ) in exchangeable K content (Srinivasarao et al, 2007;Walter et al, 2011).…”
Section: Potassium Status Of Soilsmentioning
confidence: 99%